The Effectiveness and Safety of Mesenchymal Stem Cells in the Treatment of Osteoarthritis: A Systematic Review and Meta-analysis of 28 Randomized Controlled Trials - Zhiyong Long; Mingsheng Zhang; Tianqing Zhang; Liuting Zeng; Kailin Yang; Tiejun Yang; Ganpeng Yu; Jun Li; Yang Wu; Hua Chen (Hindawi Limited, 2022)
Objective. To evaluate the effectiveness and safety of mesenchymal stem cells (MSCs) in the treatment of osteoarthritis (OA). Methods. Chinese databases (such as CNKI and SinoMed) and English databases (such as PubMed and Embase) were searched to collect randomized controlled trials (RCTs) of MSCs in the treatment of OA. The retrieval time is from inception to October 10, 2021. The literature was strictly selected according to the inclusion and exclusion criteria, data was extracted, and the quality was evaluated. RevMan 5.3 software was used for meta-analysis. STATA was used to evaluate publication bias. The registration number of this systematic review and meta-analysis is CRD42021277145. Results. A total of 28 RCTs involving 1494 participants were included. The primary outcomes showed that MSCs may reduce WOMAC pain and VAS at the 3rd-month follow-up [WOMAC pain: -3.81 (-6.95, -0.68), P=0.02. VAS: -1.11 (-1.53, -0.68), P<0.00001], and the effect lasts for at least 12 months [WOMAC pain: -4.29 (-7.12, -1.47), P=0.003. VAS: -1.77 (-2.43, -1.12), P<0.00001]. MSCs may also reduce WOMAC stiffness and physical function at the 6th-month follow-up [WOMAC stiffness: -1.12 (-2.09, -0.14), P=0.03. WOMAC physical function: -4.40 (-6.84, -1.96), P=0.0004], and the effect lasts for at least 12 months [WOMAC stiffness: -0.99 (-1.95, -0.03), P=0.04. WOMAC physical function: -3.26 (-5.91, -0.61), P=0.02]. The improvement of WOMAC pain, VAS, WOMAC stiffness, and WOMAC physical function may be clinically significant. Meanwhile, after the MSC injection, Lequesne had been reduced compared with the control group [-4.49 (-8.21, -0.77), P=0.002]. For adverse events, there is no significant difference in the safety of MSC injection and the control group [1.20 (0.97, 1.48), P=0.09]. The quality of WOMAC physical function and adverse events were moderate. Conclusion. Based on current evidence, MSCs may be a safety therapy that have a good curative effect in the treatment of OA, the onset time is no later than 3 months, and the time to maintain the curative effect is no less than 12 months. However, these results should be generalized with caution due to the generally low quality of evidence and RCTs.